Analisis Dampak Leverage (Pengungkit) Terhadap Kebangkrutan Perusahaan - Soelehan, Aan; Ramdani, Hasrul (Jurnal Ilmiah Ranggagading (JIR), 2011)
In the use of leverage which consists of operational leverage and financial leverage by the company aims to enlarge the profits generated by the company to greater than the cost of assets and resources that directly affects the increase of profits for shareholders who continue to increase in each period, although it does not cover possible earnings growth. The purpose of this research is to identify and measure the effect of the impact of the use of leverage, particularly operating leverage as measured by DOL and financial leverage as measured by using the DFL on the level of corporate bankruptcies were measured using Altman Z-Score. This research was conducted at PT. ANTAM language that is state owned company which is engaged also in industry, commerce, transportation and other services related to mineral. The research also performed at similar companies namely PT. Timah Tbk, which is involved in several business activities, namely tin mining business, coal business, and other businesses which include construction services, electricity, overhaul, and shipyards as well as exploration services as a comparison of the results of research undertaken. The results of this study is the analysis of operating leverage and financial leverage analysis of corporate bankruptcy, from the results of research conducted at PT. ANTAM Tbk found the correlation effect of using leverage against the level of corporate bankruptcies, while for the research at PT. Timah Tbk not find a relationship influence the use of leverage on corporate bankruptcy rate. It is known from the results of test and analysis of regression analysis conducted by examiners of both companies. For companies PT. ANTAM Tbk Management party should maintain good performance of the companies existing enterprise by placing conditions far from the risk of bankruptcy, while for company PT. Timah Tbk better for the Management to improve the consistency of the company in achieving the companys Z-Score in determining the level of risk of bankruptcy so there were no fluctuations in the company. Management can increase its profit by way of cost efficiency equipment that must be paid if the PT. Timah Tbk.